Intentional community: a qualitative analysis of social organization in a mixed-income neighborhood - Quist, RG (2010)
Mixed-income housing policy initiatives in the United States have attempted to reduce the social disorganization associated with concentrated urban poverty. Using a Portland, Oregon HOPE VI project as a single case study site, this thesis examined how residents’ socio-economic status, correlated closely with tenure, informed neighborhood choice, social networks, social exchange and informal social control. The latter three concepts underpin collective efficacy for children, which provided the theoretical framework for this thesis. Research methods relied on 42 in- depth interviews with parents and adolescents from rented and owned homes, 10 in-depth interviews with Housing Authority of Portland staff members and neighborhood observation over a span of four months. The study revealed differences between lower-income renters’ and higher-income owners’ framing of neighborhood choice; these frames informed subsequent approaches to social ties, social exchange, and informal social control in the neighborhood.